Bioenergetics of methanogenesis from acetate by Methanosarcina barkeri. - Peinemann, S (1988)
Methane formation from acetate by resting cells of Methanosarcina barkeri was accompanied by an increase in the intracellular ATP content from 0.9 to 4.0 nmol/mg of protein. Correspondingly, the proton motive force increased to a steady-state level of -120 mV. The transmembrane pH gradient however, was reversed under these conditions and amounted to +20 mV. The addition of the protonophore 3,5,3',4'-tetrachlorosalicylanilide led to a drastic decrease in the proton motive force and in the intracellular ATP content and to an inhibition of methane formation. The ATPase inhibitor N,N'-dicyclohexylcarbodiimide stopped methanogenesis, and the intracellular ATP content decreased. The proton motive force decreased also under these conditions, indicating that the proton motive force could not be generated from acetate without ATP. The overall process of methane formation from acetate was dependent on the presence of sodium ions; upon addition of acetate to cell suspensions of M. barkeri, a transmembrane Na+ gradient in the range of 4:1 (Na+ out/Na+ in) was established. Possible sites of involvement of the Na+ gradient in the conversion of acetate to methane and carbon dioxide are discussed. Na+ is not involved in the CO dehydrogenase reaction.